2012
DOI: 10.2298/mpns1210429a
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma in mature cystic teratoma of the ovary

Abstract: Squamous cell carcinoma in mature cystic teratoma is a rare pathologic event and in most cases it is an accidental pathohistological finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…CT scan of abdomen showed a large bilobed cystic lesion with fat-fluid level and solid calcified structure (teeth) protruding into the cyst cavity [Rokitansky protuberance]. The lesion was displacing the contrast filled bowel loops in most of the cases 5,6 .…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT scan of abdomen showed a large bilobed cystic lesion with fat-fluid level and solid calcified structure (teeth) protruding into the cyst cavity [Rokitansky protuberance]. The lesion was displacing the contrast filled bowel loops in most of the cases 5,6 .…”
Section: Disscusionmentioning
confidence: 99%
“…Cytogenetic abnormalities might precede histological changes and prolonged exposure to various carcinogens in the pelvic cavity might cause the malignant changes in mature tissue. Risk factors for malignancy in MCT include patient age,tumor size and imaging characteristics.Tumor size greater than 10cm should raise the suspicion of malignancy.In our case,the tumor diameter was 15 cm,which corresponds to literature.It is postulated that the larger size of ovarian mass indicates long standing disease process and likelihood of any of the components becoming malignant is higher 5,6 .…”
Section: Disscusionmentioning
confidence: 99%
“…It has been reported that only 2% of the cases diagnosed with mature cystic teratoma undergo a malignant change [1]. 75% of these cases with this type of germ cell tumor are further diagnosed to have squamous cell carcinoma [2]. The survival rate in these cases is around 15 to 30% over a period of 5 years [3].…”
Section: Introductionmentioning
confidence: 99%